Organizational Moral Learning: What, If Anything, Do Corporations Learn from NGO Critique? - Spitzeck, Heiko (Journal of business ethics, 2009)
While organizational learning literature has generated significant insight into the effective and efficient achievement of organizational goals as well as to the modus of learning, it is currently unable to describe moral learning processes in organizations consistently. Corporations need to learn morally if they want to deal effectively with stakeholders criticizing their conduct. Nongovernmental organizations do not ask corporations to be more effective or efficient in what they do, but to become more responsible or to learn morally. Current research on the moral aspect of organizational learning has been primarily of a theoretical nature and is in need of empirical verification. Results of a longitudinal case study as Citigroup’s conflict with the Rainforest Action Network show that current organizational moral learning theories do not fit the moral learning path observed at Citigroup. More empirical research is needed to describe organizational moral learning.